Ultrasound-Guided Supraclavicular Block: Outcome of 510 Consecutive Cases. Issue 2 (1st February 2009) - Perlas, Anahi; Lobo, Giovanni; Lo, Nick; Brull, Richard; Chan, Vincent W.S.; Karkhanis, Reena
Abstract : Introduction: Supraclavicular brachial plexus block provides consistently effective anesthesia to the upper extremity. However, traditional nerve localization techniques may be associated with a high risk of pneumothorax. In the present study, we report block success and clinical outcome data from 510 consecutive patients who received an ultrasound-guided supraclavicular block for upper extremity surgery. Methods: After institutional review board approval, the outcome of 510 consecutive patients who received an ultrasound-guided supraclavicular block for upper extremity surgery was reviewed. Real-time ultrasound guidance was used with a high-frequency linear probe. The neurovascular structures were imaged on short axis, and the needle was inserted using an in-plane technique with either a medial-to-lateral or lateral-to-medial orientation. Results: Five hundred ten ultrasound-guided supraclavicular blocks were performed (50 inpatients, 460 outpatients) by 47 different operators at different levels of training over a 24-month period. Successful surgical anesthesia was achieved in 94.6% of patients after a single attempt; 2.8% required local anesthetic supplementation of a single peripheral nerve territory; and 2.6% received an unplanned general anesthetic. No cases of clinically symptomatic pneumothorax developed. Complications included symptomatic hemidiaphragmatic paresis (1%), Horner syndrome (1%), unintended vascular punctures (0.4%), and transient sensory deficits (0.4%). Conclusions: Ultrasound-guided supraclavicular block is associated with a high rate of successful surgical anesthesia and a low rate of complications and thus may be a safe alternative for both inpatients and outpatients. Severe underlying respiratory disease and coagulopathy should remain a contraindication for this brachial plexus approach.